2012
DOI: 10.3389/fmicb.2012.00386
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase (nifH) gene expression in diazotrophic cyanobacteria in the Tropical North Atlantic in response to nutrient amendments

Abstract: The Tropical North Atlantic (TNAtl) plays a critical role in the marine nitrogen cycle, as it supports high rates of biological nitrogen (N 2 ) fixation, yet it is unclear whether this process is limited by the availability of iron (Fe), phosphate (P) or is co-limited by both. In order to investigate the impact of nutrient limitation on the N 2 -fixing microorganisms (diazotrophs) in the TNAtl, trace metal clean nutrient amendment experiments were conducted, and the expression of nitrogenase (nifH) in cyanobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…The riverine fixed N concentration is high enough in low-salinity waters to negate the advantage of N 2 fixation (Subramaniam et al, 2008), and thus fewer diazotrophs are found in these waters. Furthest from the Amazon River influence, Trichodesmium is the dominant diazotroph in the more oceanic environment, as has been observed previously (Foster et al, 2007;Turk-Kubo et al, 2012). In transitional waters between the river input and open ocean, enough fixed N has been assimilated by the community, but riverine P, Fe and Si are still in sufficiently high concentrations to create ideal conditions for diazotrophs, especially those in association with diatoms (Yeung et al, 2012;Goes et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…The riverine fixed N concentration is high enough in low-salinity waters to negate the advantage of N 2 fixation (Subramaniam et al, 2008), and thus fewer diazotrophs are found in these waters. Furthest from the Amazon River influence, Trichodesmium is the dominant diazotroph in the more oceanic environment, as has been observed previously (Foster et al, 2007;Turk-Kubo et al, 2012). In transitional waters between the river input and open ocean, enough fixed N has been assimilated by the community, but riverine P, Fe and Si are still in sufficiently high concentrations to create ideal conditions for diazotrophs, especially those in association with diatoms (Yeung et al, 2012;Goes et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Conversely, phosphate availability is known to directly influence N 2 fixation and nifH expression in natural populations of diazotrophs (Sañudo-Wilhelmy et al, 2001;Rees et al, 2006;Turk-Kubo et al, 2012), as well as the oceanic distribution of diazotrophs in general (Sohm et al, 2011). In the present study, phosphate concentrations were relatively high (for example, 0.27 μmol l − 1 and 0.26 μmol l − 1 ) in the ATS where Trichodesmiumand δ-proteobacterial-dominated communities were observed.…”
Section: Arafura Sea Coral Seamentioning
confidence: 64%
“…Therefore, other factors may have had a significant influence on diazotroph distribution and activity, for instance, dissolved iron (dFe) availability is known to limit marine N 2 fixation (see Sohm et al, 2011) and dFe additions can stimulate diazotrophic activity (Moisander et al, 2012;Turk-Kubo et al, 2012). In the western South Pacific ocean, Moisander et al, (2012) demonstrated that the abundances of unicellular diazotrophs, including UCYN-A and γ-24774A11, not only increased substantially in response to dFe amendments but also exhibited signs of iron and phosphorous co-limitation.…”
Section: Arafura Sea Coral Seamentioning
confidence: 99%
“…Currently, little is known about how UCYN-A responds to nutrient limitation. A recent study investigating the response of nifH expression of different diazotrophs to nutrient additions indicated that UCYN-A might be P limited in the tropical North Atlantic (Turk-Kubo et al, 2012). To date, there are no reports on the effect of nutrient limitation on the photosynthetic partner of UCYN-A and/or this symbiosis.…”
Section: Introductionmentioning
confidence: 94%